The puzzle of quality of life in schizophrenia: putting the pieces together with the FACE-SZ cohort. Issue 8 (23rd June 2022) - Ehrminger, Mickael; Roux, Paul; Urbach, Mathieu; André, Myrtille; Aouizerate, Bruno; Berna, Fabrice; Bohec, Anne-Lise; Capdevielle, Delphine; Chéreau, Isabelle; Clauss, Julie; Dubertret, Caroline; Dubreucq, Julien; et al.
Abstract: Background: The determinants of quality of life (QoL) in schizophrenia are largely debated, mainly due to methodological discrepancies and divergence about the concepts concerned. As most studies have investigated bi- or tri-variate models, a multivariate model accounting for simultaneous potential mediations is necessary to have a comprehensive view of the determinants of QOL. We sought to estimate the associations between cognitive reserve, cognition, functioning, insight, depression, schizophrenic symptoms, and QoL in schizophrenia and their potential mediation relationships. Methods: We used structural equation modeling with mediation analyses to test a model based on existing literature in a sample of 776 patients with schizophrenia from the FondaMental Foundation FACE-SZ cohort. Results: Our model showed a good fit to the data. We found better functioning to be positively associated with a better QoL, whereas better cognition, better insight, higher levels of depression, and schizophrenic symptoms were associated with a lower QoL in our sample. Cognitive reserve is not directly linked to QoL, but indirectly in a negative manner via cognition. We confirm the negative relationship between cognition and subjective QoL which was previously evidenced by other studies; moreover, this relationship seems to be robust as it survived in our multivariate model. It was not explained by insight as some suggested, thus the mechanism at stake remains to be explained. Conclusion: The pathways to subjective QoL in schizophrenia are complex and the determinants largely influence each other. Longitudinal studies are warranted to confirm these cross-sectional findings.